(untitled) - Sampedro, Ricardo (New York, 2004)
This book focuses on language learning as a natural way to foster cross-cultural understanding and uses a variety of hands-on techniques to tackle stereotypes and cultural barriers. The book raises awareness of global and social issues via art, music, drama, and games. It encourages reflection, critical thinking, and a questioning attitude, with many opportunities for improving communication skills through open discussion, reasoning, and putting forward different points of view
Keywords: Economic development.,English language,Developing countries,Eeveloping countries; problems, exercises, etc,spoken english,economic policy,economic conditions